Bibframe in 2015: progress and prospects of the new bibliographic model - Agenjo-Bullón, Xavier; Hernández-Carrascal, Francisca (Anuario ThinkEPI, 2016)
The most significant advances of the Bibliographic framework initiative (Bibframe) during 2015 are described, along with the proposal for a new version of the Bibframe vocabulary (Bibframe 2.0 draft specifications), and its impact on the core classes: Item, Title and Authority. Along with this, a synopsis of presentations given about Bibframe in 2015 and early 2016 is provided in order to give an overview of the status and evolution of the projects being generated around this initiative.
Keywords: Bibliographic framework initiative; Bibframe; Cataloging; Linked open data; LOD